Pengembangan Aplikasi Perhitungan Estimasi Biaya Proyek Sistem Informasi Menggunakan Metode Use Case Point, Extended Use Case Point, dan COCOMO 2 - Ananta Bintang Pradana; Satrio Agung Wicaksono; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
One of the problems faced in developing information systems is the calculation of cost estimates, the developer does not have yet a standard for determining costs in information system development. From 25000 information system projects implemented from 2011 until 2015, showed 27-31% stated that the project was successful according to (on budget , on time, satisfy), 17-22% failed (canceled or rejected), and 49-56% are challenging projects (Declared satisfactory but exceeds the budget or deadline, that is due an error use or not use existing estimation methods or models, not re-checking the input or output using Expert Judgment model, or ignorance of which method or model needs to be used in a particular condition. The way that is often used to determine the estimated cost and effort in an information system development project is by using the Expert Judgment Method due to limited time spent on the project, so that more complicated methods like COCOMO II or Use Case Points cannot be used. Based on this problem, the author created a system that helps developer to calculate the estimated cost of developing an information system project that can make it easier to calculate project cost estimates. System development using the Waterfall method. Testing method that used in this research is Basis Path Testing, Boundary Value Analysis, and User Acceptance Testing. Based on the results of testing using User Acceptance Testing, the acceptance value is 84%, which means the system is accepted by user.